Analysis of the influence of the anisotropy induced by cold rolling on duplex and super-austenitic stainless steels - Angelo Finelli; Martino Labanti (Fracture and Structural Integrity)
This report contains the results obtained from the mechanical characterization tests carried out on two different stainless steel (duplex 6%Ni, 22%Cr and super-austenitic 31%Ni, 28%Cr) used for the manufacturing of pipes which are employed in the oil production. The activity has been performed in order to evaluate the effects of anisotropy, induced by cold rolling, on the mechanical characteristics of the investigated steels, measured in the three main directions. Considering the small size of the component, the method and the specimens used for the tests were not the standard one. The procedure carried out provided the strain measurement of the specimen during testing by means of resistive strain gages, bonded on the specimens.